Modulation of secondary flows in curved serpentine micromixers. Issue 5 (4th May 2022) - Qamareen, Arees; Ansari, Mubashshir A.; Alam, Shah S.; Alazzam, Anas
Abstract: Microfluidic mixing is fundamentally important in a variety of miniaturized analysis systems. Formation of Dean vortices in curved microchannels causes inter-stream convection which enhances mixing. The aspect ratio of the microchannel plays an important role on the generation of secondary flow structures. Investigations were conducted to understand the influence of aspect ratio (AR = 0.5, 1.0, 1.5 and 2.5) on mixing performance of a curved serpentine micromixer, over a range of Reynolds numbers from 1 to 210. Qualitative and quantitative assessment of flow patterns and mixing was done through experimental and numerical techniques in the two mixing regimes namely diffusion dominated and convection-advection dominated. In general, a higher mixing performance was observed for AR = 1.5 for 50 ≤ Re ≤ 100 while AR = 0.5 was found to be the worst performing geometry. For Re > 150, all the geometries showed good mixing performance which could be due to formation of extremely strong multiple pairs of Dean vortices.